Evaluation of the ZPR1 polymorphism and its association with the habits of military police officers in Goiás (Research, Society and Development, 2024)
Several causes are related to the development of cardiovascular diseases (CVD), constitutional factors include sex, age and genetic inheritance, and acquired factors are associated with lifestyle. The objective of this study was to analyze the gene ZPR1 rs964184 (Cytosine/Guanine) and its association with the development of dyslipidemia, alcohol consumption and smoking habits in military police officers in the state of Goiás. Samples from 200 military police officers were evaluated by dosing lipid profile and qPCR (real-time polymerase chain reaction) technique. The genotypic presentation and dyslipidemia showed a rate of 62.1% for CC. Dyslipidemia associated with sex showed higher rates in male patients diagnosed with isolated hypertriglyceridemia (42.7%) and associated with reduced HDL-c levels (26.4%). In the associative parameter between the type of dyslipidemia diagnosed and alcohol consumption and smoking habit, the highest prevalences were related to isolated hypertriglyceridemia with alcohol consumption and isolated hypertriglyceridemia low HDL-c with alcohol consumption. It was observed that the G allele presents both homozygosity and heterozygosity and a tendency to be associated with hypertriglyceridemia. The rs964184 gene associated with nutritional diagnosis using BMI, the highest prevalences were found in the case group for overweight diagnoses. Statistical analysis showed that police officers who have dyslipidemia and CC and CG genotypes are more likely to be overweight. Thus, the G allele proved to be significant in police officers with reduced levels of HDL cholesterol, which contributes to a greater extent to the emergence of CVDs.